1984
DOI: 10.1103/physrevlett.53.596
|View full text |Cite
|
Sign up to set email alerts
|

Small-Angle X-Ray-Scattering Investigation of Submicroscopic Porosity with Fractal Properties

Abstract: A method is developed for analyzing the outer part of the small-angle x-ray or neutron

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
530
0
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 952 publications
(549 citation statements)
references
References 4 publications
14
530
0
5
Order By: Relevance
“…Bale and Schmidt [57] proposed a more exact criterion for a certain characteristic size of inhomogeneities: q min R  3.5.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bale and Schmidt [57] proposed a more exact criterion for a certain characteristic size of inhomogeneities: q min R  3.5.…”
Section: Resultsmentioning
confidence: 99%
“…Bale and Schmidt [57] have also shown that for porous materials in which the interfaces are surface fractals with a fractal dimension 2 ≤ D s < 3, the scattering intensity depends on the momentum transfer in a power law form:…”
Section: Resultsmentioning
confidence: 99%
“…20 The fractal nature of the system can be delineated from the power-law exponents derived from the scattering data. [21][22][23] If I(Q) varies as Q Ϫp in a Q region, where QR g ӷ1, then pϽ3 denotes that the scattering system may be a mass fractal 22,23 and 3ϽpϽ4 corresponds to a surface fractal. 21 The fractal dimension of the surface, D s , is D s ϭ6Ϫp.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] If I(Q) varies as Q Ϫp in a Q region, where QR g ӷ1, then pϽ3 denotes that the scattering system may be a mass fractal 22,23 and 3ϽpϽ4 corresponds to a surface fractal. 21 The fractal dimension of the surface, D s , is D s ϭ6Ϫp. 21 The extent of deviation of p from 4 can be used as a qualitative measure of the surface roughness.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation